Microprudential Regulation in a Dynamic Model of Banking - De Nicolò, Gianni; Gamba, Andrea; Lucchetta, Marcella (Review of Financial Studies, 2014)
This paper studies the quantitative impact of microprudential bank regulations on bank lending and value metrics of efficiency and welfare in a dynamic model of banks that are financed by debt and equity, undertake maturity transformation, are exposed to credit and liquidity risks, and face financing frictions. We show that (1) there exists an inverted U-shaped relationship between bank lending, welfare, and capital requirements, (2) liquidity requirements unambiguously reduce lending, efficiency, and welfare, and (3) resolution policies contingent on observed capital, such as prompt corrective action, dominate in efficiency and welfare terms (noncontingent) capital and liquidity requirements.